Linking αMSH with PPARγ in B16‐F10 melanoma. (12th September 2012) - Maresca, Vittoria; Flori, Enrica; Camera, Emanuela; Bellei, Barbara; Aspite, Nicaela; Ludovici, Matteo; Catricalà, Caterina; Cardinali, Giorgia; Picardo, Mauro
Summary We have discovered a new α‐melanocyte stimulating hormone (α‐MSH)/peroxisome proliferator activated receptor‐γ (PPAR‐γ) connection in B16‐F10 cells. Both PPAR‐γ up‐regulation and its induction as an active transcription factor were observed in response to α‐MSH. The α‐MSH/PPAR‐γ connection influenced both pigmentation and proliferation. The forskolin‐stimulated cAMP/PKA pathway was not able to induce either PPAR‐γ translocation into the nucleus or PPAR‐γ transcriptional activity. As the melanocortin‐1 receptor, the specific receptor for the α‐MSH, is a G‐protein coupled receptor, we wondered whether the phosphatidylinositol [PI(4, 5)P2/PLCβ] signal pathway was involved in mediating the α‐MSH‐dependent PPAR‐γ activation. Employing inhibitors of PI(4, 5)P2/PLCβ pathway, the results of our experiments suggested that this pathway was promoted by α‐MSH and that α‐MSH played a role in mediating PPAR‐γ activation. We have demonstrated, for the first time, that α‐MSH induces the PI(4, 5)P2/PLCβ pathway, through analysis of the basic steps of the pathway. The α‐MSH effect on PPAR‐γ was independent of animal species and was not correlated with the physio‐pathological status.